Sex differences in cardiovascular research. (14th October 2021) - Millenaar, D N; Dillmann, M; Fehlmann, T; Flohr, A; Mehran, R; Al-Lamee, R; Lauder, L; Ukena, C; Boehm, M; Keller, A; Mahfoud, F
Abstract: Background: Women are underrepresented in cardiovascular publications. We sought to investigate sex-specific differences in cardiovascular research over the last decade. Methods and results: All 387, 463 cardiovascular publications between 2010–2019 were retrieved from Web-of-Science and analyzed regarding the authors' sex, the average impact factor (IF), the number of citations, co-authors per article, and international collaborations. The number of cardiovascular research articles increased between 2010–2019 from 19, 960 to 29, 604 articles per year. The number of articles written by female first authors increased by 48.3% (6434 articles in 2010 and 11, 343 articles in 2019) and by 35.0% for male first authors (13, 526 articles in 2010 and 18, 261 articles in 2019). The last/senior author was more likely to be female in articles with female first authors compared with male first authors (28.2% vs. 14.1%; odds ratio 2.48, 95% confidence interval 2.43–2.53, p<0.001). The average IF for articles by female first authors was lower compared to male (3.1±3.8 vs. 3.5±4.9, p<0.001). Likewise, the H-Index was lower for female than male first authors (1.07±0.74 vs. 1.25±0.98, p<0.001), as was the number of citations per articles (14.0±31.1 vs. 18.0±68.8 citations, p<0.001). Female first authors had fewer co-authors per article than their male peers (7.4±19.6 vs. 8.2±35.2; p<0.001) and were less represented in articles with >15 co-authors (3, 623 articles by female and 8, 941 by male first authors; ratio female to male 0.41). Scientific advancement as the ratio between female to male first authorships was highest in publications from Latin America (ratio 0.92) and lowest in Asia (ratio 0.40). Female authorship articles reached the highest IF in North America (average IF 3.7), the lowest Africa (average IF 1.8). Conclusions: Publications in cardiovascular research have increased over the last decade, particularly by female authors. Female researchers are cited less often compared with their male peers and publish with fewer co-authors. The IF remains lower for articles by female researchers. Efforts to further increase women-led research activities are needed FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): German Cardiac SocietyGerman Research Foundation (DFG)